Process integration. Tests and application of different tools on an integrated steelmaking site - Grip, Carl-Erik; Larsson, Mikael; Harvey, Simon; Nilsson, Lars (2011)
The energy network in Luleå consists of the steel plant, heat and power production and district heating. Global system studies are necessary to avoid sub-optimization and to deliver energy and/or material efficiency. SSAB began work with global simulation models in 1978. After that several more specialized process integration tools have been tested and used: Mathematical programming using a MILP method, exergy analysis and Pinch analysis. Experiences and examples of results with the different methods are given and discussed. Mathematical programming has been useful to study problems involving the total system with streams of different types of energy and material and reaction between them. Exergy is useful to describe energy problems involving different types of energy, e.g. systematic analysis of rest energies. Pinch analysis has been used especially on local systems with streams of heat energy and heat exchange between them.